МЕТОДОЛОГИЯ КОНТРОЛЯ И ОЦЕНКИ МЕТОДОЛОГИИ В СИСТЕМЕ СЛУХА - Оразов, Ш.Б.; Мамутов, К.Т. (SCIENCE and SOCIETY, 2020)
The article deals with the methodological system of monitoring and evaluating the teaching process of trainers, as well as pedagogical observations, advantages and disadvantages of the comparative analysis lesson.